(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the extent of the impact of the legal regulation of green banking in achieving agricultural development, diagnosing the level of adoption of green banking by Iraqi banks, achieving food security, increasing the contribution of the agricultural sector to the agricultural gross domestic product, and demonstrating the role of the legal regulation of green banking in achieving agricultural development. A sample was taken from the Agricultural Cooperative Bank located in Baghdad for the period from 2010-2022. The researcher relied on the descriptive analytical approach to the research variables for the available data. The research was based on the following hypothesis (there is a significant effect between the total green banking loans granted under its legal regulation and the gross domestic product to achieve agricultural development). The hypothesis was proven according to the approved statistical analysis. The most prominent conclusions reached by the researcher are that the bank seeks to qualify a special department concerned with following up on the procedures related to green banking. The most prominent results reached by the research are that the Agricultural Cooperative Bank provided the legal framework for agricultural credit provided by it in the form of multiple instructions and according to the type of credit and possesses human and financial capabilities that enable it to play a major role in preserving the environment, supporting society and meeting the desires and expectations of customers. It presented the most important solutions that help advance the agricultural sector and the extent of their interest in environmental and societal aspects in a way that achieves a competitive advantage for them and the role that green banks can play in achieving agricultural development goals.